A preventive care strategy to reduce moderate or severe acute kidney injury after major surgery (BigpAK-2); a multinational, randomised clinical trial - Zarbock, Alexander; Ostermann, Marlies; Forni, Lui; Bode, Christian; Wild, Lennart; Putensen, Christian; Roux, Diego Parise; Martín, Elena Elías; Arndt, Christian; Rahmel, Tim; de Rosa, Silvia; Monard, Céline; et al. (The lancet, 2025)
Background - Acute kidney injury (AKI) is a common and important complication of major surgery, yet recommended preventive care is rarely administered. We used urinary biomarkers to identify patients at high risk of AKI and implemented a preventive care strategy to reduce AKI within 72 h after major surgery. - Methods - BigpAK-2 was a multicentre randomised clinical trial done in 34 hospitals in Europe. Patients (aged ≥18 years) undergoing major surgery at high risk for AKI identified by predefined clinical risk factors and tubular stress biomarkers were randomly assigned to usual care or a preventive care strategy as per recommendations by the Kidney Disease Improving Global Outcome guidelines: advanced hemodynamic monitoring, optimisation of volume status and haemodynamics, avoidance of nephrotoxic drugs and radiocontrast agents, and prevention of hyperglycaemia. The primary outcome was the occurrence of moderate or severe AKI within 72 h after surgery, assessed in the intention-to-treat population. Safety was assessed by comparing rates of adverse events between groups. This trial is registered with ClinicalTrials.gov, NCT04647396. - Findings - From Nov 25, 2020, to June 21, 2024, 7873 patients were screened and 1180 (15·0%) were randomly assigned (589 [49·9%] to the intervention group and 591 [50·1%] to the control group). Among the 1176 patients available for the primary endpoint analysis, moderate or severe AKI occurred in 84 (14·4%) patients in the intervention group and in 131 (22·3%) patients in the control group (odds ratio 0·57 [95% CI 0·40-0·79; p=0·0002; number needed to treat 12 [7-33]). There were no differences in adverse events. The most common adverse events were atrial fibrillation (50 [8·8%] in the intervention group vs 56 (9·7%) in the control group), hemodynamically relevant arrhythmias (41 [7·2%] in the intervention group vs 50 [8·6%] in the control group), significant bleeding or haemorrhage (34 [6·0%] in the intervention group vs 31 [5·3%] in the control group), and unplanned return to the operating room (29 [5·1%] in the intervention vs 38 [6·5%] in the control group). - Interpretation - Among adults at high risk for AKI undergoing major surgery, a preventive care strategy consisting of supportive measures and avoidance of nephrotoxins significantly reduced the occurrence of moderate or severe AKI without increasing adverse events. - Funding - BioMérieux.
Online verfügbar: 13. November 2025, Artikelversion: 11. Dezember 2025
Gesehen am 20.02.2026